Recent Update on Topical Drug Delivery Systems: Emulgel - Lilhare, Kajal T.; Borkar, Shilpa S.; R. Baheti, Jagdish (Asian Journal of Pharmaceutical Research and Development, 2023)
Emulgel is an emerging topical drug delivery system that, if more effort is devoted to its formulation and development with more topically active drugs, will prove to be a boon to skin care and cosmetology. Emulgels are both O/W or W/O emulsions which might be gelled with the aid of mixing with a gelling agent. Incorporating the emulgel increases its stability and makes it controlled release system. Due to the lack of excess oil bases and insoluble excipients, it exhibits better drug release compared to other topical drug delivery systems. The presence of the gel phase makes it non-greasy and promotes good affected person cooperation. Those reviews provide knowledge approximately Emulgel such as its properties, benefits, formulations and its current research advances. All elements consisting of the choice of gelling agent, oil agent, emulsifiers affecting the stability and effectiveness of Emulgel are discussed. All rationales are defined in accordance with study conducted via numerous scientists. After anin depth examine, it could be concluded that Emulgels appear to be a better and greater effective drug delivery system compared to other topical drug delivery systems. A complete analysis of the rheological and release properties will offer insight into the capacity use of the Emulgel formulation as a drug delivery System.